Sea Lice ( Lepeophtheirus salmonis ) Harbour Putative Fish Pathogens: Insights From Illumina and Nanopore Sequencing - B. Klimesova; N. M. Ruane; R. Domingo‐Bretón; F. Moroni; F. Naya‐Català; J. Pérez‐Sánchez; K. O'Dwyer; O. Lyashevska; H. Rodger; A. Talbot (Journal of Fish Diseases, 2026)
Ectoparasites that penetrate host skin can act as biological or mechanical vectors for pathogens and, in some cases, serve as reservoirs. Crustacean ectoparasites of fish are potential vectors of pathogens, which is especially relevant for obligate pathogens (e.g., Aeromonas salmonicida ) with limited seawater survival. Sea lice ( Lepeophtheirus salmonis ), affecting Atlantic salmon, cause dermal damage and can facilitate secondary infections, resulting in economic losses. While the physical impact of sea lice is well known, their role in pathogen transmission is less clear. The gut bacterial microbiome of lice collected over four months from a salmon farm in Ireland was analysed using Illumina MiSeq and Oxford Nanopore Technologies (ONT) PromethION sequencing for comparison. Illumina and Nanopore sequencing identified 15 and 24 genera of known fish pathogens, respectively. Moreover, Nanopore data revealed up to 15 putative pathogenic species, including Tenacibaculum maritimum , T. dicentrarchi and Vibrio anguillarum , causative agents of tenacibaculosis and vibriosis. The results of this study provide a gut bacterial microbiome characterisation of L. salmonis in a commercial aquaculture setting and demonstrate the potential of sea lice to act as pathogen vectors or reservoirs. These findings have important implications for pathogen surveillance, management, and prevention strategies in salmon aquaculture.

Flame retardant biomarker changes with furniture replacement after flammability standard update - Kathleen R. Attfield; Kimberly Berger; Robin E. Dodson; Deborah H. Bennett; Kathryn M. Rodgers; Rebecca Moran; Tasha Stoiber; Yunzhu Wang; Songmei Gao; Sabrina Crispo Smith; June-Soo Park; Arlene Blum; et al. (Environmental Pollution, 2026)

Wildfires under changing climate, and their environmental and health impacts - Shiv Bolan; Shailja Sharma; Santanu Mukherjee; Daniel F. Gomez Isaza; Essie M. Rodgers; Pingfan Zhou; Deyi Hou; Facundo Scordo; Sudeep Chandra; Kadambot H. M. Siddique; Nanthi Bolan (Journal of Soils and Sediments, 2025)
Purpose Extreme weather events including drought, flooding, and wildfires resulting from climate change can impact ecosystems. Various toxic substances are emitted during wildfires, such as particulate matter and volatile organic compounds, as the frequency and intensity of wildfires rise with climate change. This review aims to focus on the effects of wildfires on environmental health covering contaminants in soil, aquatic and atmospheric environment. Materials and methods A thorough literature search was conducted in Web of Science Core Collections with the following keywords: “wildfire” OR “volatile organic compounds” OR “pollution” OR “contamination” OR “terrestrial pollution” OR “aquatic pollution” OR “atmospheric pollution”. PRISMA flow chart was used to highlight the review's content and provide a more thorough synthesis of relevant studies. Results and discussion Various studies have shown how wildfire emissions affect the public health, although handful information available regarding the environmental health impacts of smoke emissions during wildfires. The post-wildfire trace elemental concentrations and speciation are notably linked to plant species, geology, and topography. Recent studies found increased levels of nitrogen (N), phosphorus (P), dissolved organic carbon (DOC), suspended solids, and water turbidity in lakes within wildfire-burnt watersheds. The response of individual ecosystems to wildfire depends on proximity to the fire, fire characteristics, fuel fee material burned, the effect of fundamental drivers of water quality. Conclusions The findings of this review will encourage and strengthen collaboration between the scientific community and regulatory agencies to better understand how erratic weather events, such as wildfires, may affect the health of people and animals. Graphical Abstract

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

The effect of a digital health coaching and health education protocol on cognition in adults at-risk for Alzheimer’s - Anthony Campitelli; Joshua L. Gills; Megan D. Jones; Sally Paulson; Jennifer Myers; Kelsey Bryk; Erica N. Madero; Jordan M. Glenn; Charlie H. Rodgers; Jenova A. Kempkes; Michelle Gray (GeroScience, 2023)
Several modifiable lifestyle factors have been linked to cognitive ability and the risk of developing Alzheimer’s disease and related dementias (ADRD). Health coaching (HC) is an intervention that addresses lifestyle factors associated with cognition. The effectiveness of an HC protocol was evaluated and compared with a health education (HE) intervention, representing the current standard of care, in a sample of 216 adults between the ages of 45 and 75 years who were at-risk for developing ADRD. Outcomes examined were global cognition, neuropsychological cognition, and Alzheimer’s risk. HC participants received personalized coaching from a health coach focusing on nutrition, physical activity, sleep, stress, social engagement, and cognitive activity. HE participants received biweekly education materials focusing on the same modifiable lifestyle factors addressed by HC. Participants were assessed at baseline and again 4 months later. Self-reported global cognition scores improved only in the HC group (16.18 to 15.52, p = .03) and neuropsychological cognitive ability improved in the HE group (104.48 to 108.76, p < .001). When non-adherence in the HC group was accounted for, however, the mean change in neuropsychological score was similar between groups ( p > .05), self-reported global cognition demonstrated an even larger mean improvement in the HC group (16.20 to 15.41, p = .01), and the HC group saw an improvement in ADRD protective risk score (− 10.39 to − 11.45, p = .007). These results indicate that HC and HE can both improve cognition, but HC may be more effective and may yield increased protection against ADRD risk.

Distribution and source assignments of polycyclic aromatic and aliphatic hydrocarbons in sediments and biota of the Lafayette River, VA - Nathaniel Maynard; H. Rodger Harvey (Environmental Science and Pollution Research, 2023)

Sources and concentrations of methane, ethane, and CO2 in deep aquifers of the Surat Basin, Great Artesian Basin - J.K. Pearce; H. Hofmann; K. Baublys; S.D. Golding; I. Rodger; P. Hayes (International Journal of Coal Geology, 2023)

Gray whale density during seismic surveys near their Sakhalin feeding ground - Glenn Gailey; Mikhail Zykov; Olga Sychenko; Alexander Rutenko; Arny L. Blanchard; Lisanne Aerts; Rodger H. Melton (Environmental Monitoring and Assessment, 2022)
Oil and gas development off northeastern Sakhalin Island, Russia, has exposed the western gray whale population on their summer-fall foraging grounds to a range of anthropogenic activities, such as pile driving, dredging, pipeline installation, and seismic surveys. In 2015, the number of seismic surveys within a feeding season surpassed the level of the number and duration of previous seismic survey activities known to have occurred close to the gray whales’ feeding ground, with the potential to cause disturbance to their feeding activity. To examine the extent that gray whales were potentially avoiding areas when exposed to seismic and vessel sounds, shore-based teams monitored the abundance and distribution of gray whales from 13 stations that encompassed the known nearshore feeding area. Gray whale density was examined in relation to natural (spatial, temporal, and prey energy) and anthropogenic (cumulative sound exposure from vessel and seismic sounds) explanatory variables using Generalized Additive Models (GAM). Distance from shore, water depth, date, and northing explained a significant amount of variation in gray whale densities. Prey energy from crustaceans, specifically amphipods, isopods, and cumaceans also significantly influenced gray whale densities in the nearshore feeding area. Increasing cumulative exposure to vessel and seismic sounds resulted in both a short- and longer-term decline in gray whale density in an area. This study provides further insights about western gray whale responses to anthropogenic activity in proximity to and within the nearshore feeding area. As the frequency of seismic surveys and other non-oil and gas anthropogenic activity are expected to increase off Sakhalin Island, it is critical to continue to monitor and assess potential impacts on this endangered population of gray whales.

Western gray whale behavioral response to seismic surveys during their foraging season - Glenn Gailey; Olga Sychenko; Mikhail Zykov; Alexander Rutenko; Arny Blanchard; Rodger H. Melton (Environmental Monitoring and Assessment, 2022)
Gray whales utilizing their foraging grounds off northeastern Sakhalin Island, Russia, have been increasingly exposed to anthropogenic activities related to oil and gas development over the past two decades. In 2015, four seismic vessels, contracted by two operators, conducted surveys near and within the gray whale feeding grounds. Mitigation and monitoring plans were developed prior to the survey and implemented in the field, with real-time data transfers to assist the implementation of measures aimed at minimizing impacts of acoustic exposure. This study examined the behavioral response of gray whales relative to vessel proximities and sounds generated during seismic exploration. Five shore-based teams monitored gray whale behavior from 1 June to 30 September using theodolite tracking and focal follow methodologies. Behavioral data were combined with acoustic and benthic information from studies conducted during the same period. A total of 1270 tracks (mean duration = 0.9 h) and 401 focal follows (1.1 h) were collected with gray whales exposed to sounds ranging from 59 to 172 dB re 1 μPa 2 SPL. Mixed models were used to examine 13 movement and 10 respiration response variables relative to “natural,” acoustic, and non-acoustic explanatory variables. Water depth and behavioral state were the largest predictors of gray whale movement and respiration patterns. As vessels approached whales with increasing seismic/vessel sound exposure levels and decreasing distances, several gray whale movement and respiration response variables significantly changed (increasing speed, directionality, surface time, respiration intervals, etc.). Although the mitigation measures employed could have reduced larger/long-term responses and sensitization to the seismic activities, this study illustrates that mitigation measures did not eliminate behavioral responses, at least in the short-term, of feeding gray whales to the activities.

Seismic surveys near gray whale feeding areas off Sakhalin Island, Russia: assessing impact and mitigation effectiveness - Lisanne Aerts; Michael R. Jenkerson; Vladimir E. Nechayuk; Glenn Gailey; Roberto Racca; Arny L. Blanchard; Lisa K. Schwarz; H. Rodger Melton (Environmental Monitoring and Assessment, 2022)
In 2015, two oil and gas companies conducted seismic surveys along the northeast coast of Sakhalin Island, Russia, near western gray whale ( Eschrichtius robustus ) feeding areas. This population of whales was listed as Critically Endangered at the time of the operations described here but has been reclassified as Endangered since 2018. The number and duration of the 2015 seismic surveys surpassed the level of previous seismic survey activity in this area, elevating concerns regarding disturbance of feeding gray whales and the potential for auditory injury. Exxon Neftegas Limited (ENL) developed a mitigation approach to address these concerns and, more importantly, implemented a comprehensive data collection strategy to assess the effectiveness of this approach. The mitigation approach prioritized completion of the seismic surveys closest to the nearshore feeding area as early in the season as possible, when fewer gray whales would be present. This was accomplished by increasing operational efficiency through the use of multiple seismic vessels and by establishing zones with specific seasonal criteria determining when air gun shutdowns would be implemented. These zones and seasonal criteria were based on pre-season modeled acoustic footprints of the air gun array and on gray whale distribution data collected over the previous 10 years. Real-time acoustic and whale sighting data were instrumental in the implementation of air gun shutdowns. The mitigation effectiveness of these shutdowns was assessed through analyzing short-term behavioral responses and shifts in gray whale distribution due to sound exposure. The overall mitigation strategy of an early survey completion was assessed through bioenergetics models that predict how reduced foraging activity might affect gray whale reproduction and maternal survival. This assessment relied on a total of 17 shore-based and 5 vessel-based teams collecting behavior, distribution, photo-identification, prey, and acoustic data. This paper describes the mitigation approach, the implementation of mitigation measures using real-time acoustic and gray whale location data, and the strategy to assess impacts and mitigation effectiveness.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Conspecific brood parasitism in an upland-nesting bird: cues parasites use to select a nest - Natalie J. Thimot; Rodger D. Titman; Kyle H. Elliott; Shawn R. Craik (Behavioral Ecology and Sociobiology, 2020)

Low-intensity repetitive transcranial magnetic stimulation over prefrontal cortex in an animal model alters activity in the auditory thalamus but does not affect behavioural measures of tinnitus - Wilhelmina H. A. M. Mulders; K. Leggett; V. Mendis; H. Tarawneh; J. K. Wong; J. Rodger (Experimental Brain Research, 2019)

Characterization of a large sex determination region in Salix purpurea L. (Salicaceae) - Ran Zhou; David Macaya-Sanz; Eli Rodgers-Melnick; Craig H. Carlson; Fred E. Gouker; Luke M. Evans; Jeremy Schmutz; Jerry W. Jenkins; Juying Yan; Gerald A. Tuskan; Lawrence B. Smart; Stephen P. DiFazio (Molecular Genetics and Genomics, 2018)

Costs and response to conspecific brood parasitism by colonial red-breasted mergansers - Shawn R. Craik; Rodger D. Titman; Jean-Pierre L. Savard; Mohammadi Kaouass; Natalie Thimot; Kyle H. Elliott; Éric Tremblay (Journal of Ethology, 2018)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Solar Photocatalysis Using Fixed-Film TiO2 for Microcystins from Colonial Microcystis aeruginosa - Ciera M. Kinley; Maas Hendrikse; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Relationship among aqueous copper half-lives and responses of Pimephales promelas to a series of copper sulfate pentahydrate concentrations - Alyssa J. Calomeni; Ciera M. Kinley; Tyler D. Geer; Kyla J. Iwinski; Maas Hendrikse; John H. Rodgers (Ecotoxicology, 2018)

Cold tolerance and invasive potential of the redbay ambrosia beetle (Xyleborus glabratus) in the eastern United States - John P. Formby; John C. Rodgers; Frank H. Koch; Natraj Krishnan; Donald A. Duerr; John J. Riggins (Biological Invasions, 2018)

Microcystin-LR Degradation Following Copper-Based Algaecide Exposures - Ciera M. Kinley; Kyla J. Iwinski-Wood; Tyler D. Geer; Maas Hendrikse; Andrew D. McQueen; Alyssa J. Calomeni; Jenny Liang; Vanessa Friesen; Monique C. Simair; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

Characterization of Copper Algaecide (Copper Ethanolamine) Dissipation Rates Following Pulse Exposures - Alyssa J. Calomeni; Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Maas Hendrikse; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Nitrogen subsidies in glacial meltwaters have altered planktonic diatom communities in lakes of the US Rocky Mountains for at least a century - Krista E. H. Slemmons; Markie L. Rodgers; Jeffery R. Stone; Jasmine E. Saros (Hydrobiologia, 2017)

Changing relative crank angle increases the metabolic cost of leg cycling - Asher H. Straw; Wouter Hoogkamer; Rodger Kram (European Journal of Applied Physiology, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Predicting In Situ Responses of Taste- and Odor-Producing Algae in a Southeastern US Reservoir to a Sodium Carbonate Peroxyhydrate Algaecide Using a Laboratory Exposure-Response Model - Tyler D. Geer; Alyssa J. Calomeni; Ciera M. Kinley; Kyla J. Iwinski; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Technical pre‐analytical effects on the clinical biochemistry of Atlantic salmon ( Salmo salar L.) - M Braceland; K Houston; A Ashby; C Matthews; H Haining; H Rodger; P D Eckersall (Journal of Fish Diseases, 2017)
Clinical biochemistry has long been utilized in human and veterinary medicine as a vital diagnostic tool, but despite occasional studies showing its usefulness in monitoring health status in Atlantic salmon ( Salmo salar L.), it has not yet been widely utilized within the aquaculture industry. This is due, in part, to a lack of an agreed protocol for collection and processing of blood prior to analysis. Moreover, while the analytical phase of clinical biochemistry is well controlled, there is a growing understanding that technical pre‐analytical variables can influence analyte concentrations or activities. In addition, post‐analytical interpretation of treatment effects is variable in the literature, thus making the true effect of sample treatment hard to evaluate. Therefore, a number of pre‐analytical treatments have been investigated to examine their effect on analyte concentrations and activities. In addition, reference ranges for salmon plasma biochemical analytes have been established to inform veterinary practitioners and the aquaculture industry of the importance of clinical biochemistry in health and disease monitoring. Furthermore, a standardized protocol for blood collection has been proposed.

The epidemiology of pancreas disease in salmonid aquaculture: a summary of the current state of knowledge - M D Jansen; B Bang Jensen; M F McLoughlin; H D Rodger; T Taksdal; H Sindre; D A Graham; A Lillehaug (Journal of Fish Diseases, 2017)
Pancreas disease ( PD ) is a viral disease caused by Salmonid alphavirus ( SAV ) that affects farmed Atlantic salmon ( Salmo salar L.) and rainbow trout ( Oncorhynchus mykiss (Walbaum)) in the seawater phase. Since its first description in Scotland in 1976, a large number of studies have been conducted relating to the disease itself and to factors contributing to agent spread and disease occurrence. This paper summarizes the currently available, scientific information on the epidemiology of PD and its associated mitigation and control measures. Available literature shows infected farmed salmonids to be the main reservoir of SAV . Transmission between seawater sites occurs mainly passively by water currents or actively through human activity coupled with inadequate biosecurity measures. All available information suggests that the current fallowing procedures are adequate to prevent agent survival within the environment through the fallowing period and thus that a repeated disease outbreak at the same site is due to a new agent introduction. There has been no scientific evaluation of currently used on‐site biosecurity measures, and there is limited information on the impact of available mitigation measures and control strategies.

Effects of Acid Volatile Sulfides (AVS) from Na2S-Amended Sediment on Hyalella azteca - Andrew D. McQueen; Ciera M. Kinley; Kyla J. Iwinski; Alyssa J. Calomeni; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Photocatalysis of a Commercial Naphthenic Acid in Water Using Fixed-Film TiO2 - Andrew D. McQueen; Ciera M. Kinley; Rebecca L. Kiekhaefer; Alyssa J. Calomeni; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2016)

Sediment Copper Concentrations, In Situ Benthic Invertebrate Abundance, and Sediment Toxicity: Comparison of Treated and Untreated Coves in a Southern Reservoir - Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Pathology and mortality associated with the mauve stinger jellyfish P elagia noctiluca in farmed A tlantic salmon S almo salar L. - M Marcos‐López; S O Mitchell; H D Rodger (Journal of Fish Diseases, 2016)

Genomic comparison of virulent and non‐virulent S treptococcus agalactiae in fish - C M J Delannoy; R N Zadoks; M Crumlish; D Rodgers; F A Lainson; H W Ferguson; J Turnbull; M C Fontaine (Journal of Fish Diseases, 2016)
Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex ( CC ) 7, notably its namesake sequence type ( ST ) 7, or by non‐haemolytic strains of CC 552, including the globally distributed ST 260. In contrast, CC 23, including its namesake ST 23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST 23 is virulent in fish and to identify genomic markers of fish adaptation of S . agalactiae . Intraperitoneal challenge of Nile tilapia, O reochromis niloticus ( L innaeus), showed that ST 260 is lethal at doses down to 10 2 cfu per fish, whereas ST 23 does not cause disease at 10 7 cfu per fish. Comparison of the genome sequence of ST 260 and ST 23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S . agalactiae that have the ability to infect fish ( CC 7 and CC 552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR ‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.

Lace plant ethylene receptors, AmERS1a and AmERS1c, regulate ethylene-induced programmed cell death during leaf morphogenesis - Gaolathe Rantong; Rodger Evans; Arunika H. L. A. N. Gunawardena (Plant Molecular Biology, 2015)

Biography - R W Hardy; H Rodger (Journal of Fish Diseases, 2015)

Analysis of Algaecide Exposures: an Evaluation of the I3 − Method to Measure Sodium Carbonate Peroxyhydrate Algaecides - Ciera M. Kinley; John H. Rodgers; Kyla J. Iwinski; Andrew D. McQueen; Alyssa J. Calomeni (Water, Air, & Soil Pollution, 2015)

An outbreak of francisellosis in wild‐caught C eltic S ea A tlantic cod, G adus morhua L., juveniles reared in captivity - N M Ruane; M Bolton‐Warberg; H D Rodger; D J Colquhoun; M Geary; S J McCleary; K O'Halloran; K Maher; D O'Keeffe; L Mirimin; K Henshilwood; F Geoghegan; et al. (Journal of Fish Diseases, 2015)

Responses of Planktothrix agardhii and Pseudokirchneriella subcapitata to Copper Sulfate (CuSO4 · 5H2O) and a Chelated Copper Compound (Cutrine®-Ultra) - Alyssa Calomeni; John H. Rodgers; Ciera M. Kinley (Water, Air, & Soil Pollution, 2014)

Clinical cardiomyopathy syndrome in Atlantic salmon, Salmo salar L. - H D Rodger; S J McCleary; N M Ruane (Journal of Fish Diseases, 2014)

Biogeochemical Process-Based Design and Performance of a Pilot-Scale Constructed Wetland for Arsenic Removal from Simulated Bangladesh Groundwater - Jeffrey P. Schwindaman; James W. Castle; John H. Rodgers (Water, Air, & Soil Pollution, 2014)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

Bioavailability and Analytical Measurement of Copper Residuals in Sediments - Ben E. Willis; Bethany L. Alley; John H. Rodgers (Water, Air, & Soil Pollution, 2013)

A modified Latent Class Model assessment of human papillomavirus-based screening tests for cervical lesions in women with atypical glandular cells: a Gynecologic Oncology Group study - Randy L. Carter; Le Kang; Kathleen M. Darcy; James Kauderer; Shu-Yuan Liao; William H. Rodgers; Joan L. Walker; Heather A. Lankes; S. Terence Dunn; Eric J. Stanbridge (Cancer Causes & Control, 2012)

Geographical distribution of salmonid alphavirus subtypes in marine farmed Atlantic salmon, Salmo salar L., in Scotland and Ireland - D A Graham; E Fringuelli; H M Rowley; D Cockerill; D I Cox; T Turnbull; H Rodger; D Morris; M F Mc Loughlin (Journal of Fish Diseases, 2012)
Sequence data from salmonid alphavirus (SAV) strains obtained from farmed marine Atlantic salmon, Salmo salar L. , over a 20‐year period between 1991 and 2011 was reviewed to examine the geographical distribution of the genetically defined SAV subtypes in twelve regions across Ireland and Scotland. Of 160 different Atlantic salmon SAV strains examined, 62 belonged to subtype 1, 28 to subtype 2, 34 to subtype 4, 35 to subtype 5 and 1 to subtype 6. SAV subtypes 1, 4 and 6 were found in Ireland, while subtypes 1, 2, 4 and 5 were found in Scotland. In the majority of regions, there was a clear clustering of subtypes, with SAV subtype 1 being the dominant subtype in Ireland overall, as well as in Argyll and Bute in Scotland. SAV subtype 2 predominated in the Shetland and Orkney Islands. The emergence in Atlantic salmon of subtype 2 strains typically associated with sleeping disease in rainbow trout in Argyll and Bute, strongly suggesting transmission of infection between these species, was noted for the first time. SAV subtype 4 was the most common subtype found in the southern Western Isles, while SAV subtype 5 predominated in the northern Western Isles and north‐west mainland Scotland. No single strain was dominant on sites in the western Highlands, with a number of sites in this region in particular having more than one subtype detected in different submissions. The significance of these results in relation to aspects of the epidemiology of infection, including transmission, biosecurity and wildlife reservoirs are discussed and knowledge gaps identified.

Detection of Neoparamoeba perurans by duplex quantitative Taqman real‐time PCR in formalin‐fixed, paraffin‐embedded Atlantic salmonid gill tissues - E Fringuelli; A W Gordon; H Rodger; M D Welsh; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative duplex real‐time PCR for the detection of Neoparamoeba perurans and the elongation factor α 1 gene (ELF) of Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), are described. A set of primers and probe was designed to amplify a 139‐bp fragment specific to the N. perurans 18S rRNA gene. The test was shown to be very sensitive, being able to detect as little as 13.4 DNA copies per μL corresponding to 0.15 fg of template DNA. In addition, the reaction that detected N. perurans was found to have a high degree of repeatability and reproducibility, to have a linear dynamic range ( R 2 = 0.999) extending over 5 log 10 dilutions and to have a high efficiency (104%). The assay was applied to DNA samples extracted from 48 formalin‐fixed, paraffin‐embedded (FFPE) salmon gill tissues showing varying degrees of gill histopathology and amoebic gill disease (AGD)‐type histopathology ranging from absent to severe (each scored 0–3). Neoparamoeba perurans DNA was detected in all the blocks where AGD‐type histopathology was diagnosed microscopically and in 43.6% of the blocks showing signs of gill pathology. The association between parasitic load and gill histopathology and AGD‐type histopathology severity was also investigated. This study also describes the development and the application of a second real‐time PCR for the generic detection of Neoparamoeba spp ., Page, 1987. A set of primers and probe conserved among the Neoparamoeba spp. was designed to amplify a 150‐bp fragment within the 18S rRNA gene. Applied to N. perurans‐ negative gill tissues, the method was used to exclude the presence of other Neoparamoeba spp. in those blocks where gill pathology was observed microscopically.

Development of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum and its application to field samples - E Fringuelli; P D Savage; A Gordon; E J Baxter; H D Rodger; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum are described. A set of primers and probe was designed to amplify a 155‐bp fragment specific to the T. maritimum 16S rRNA gene. The test was shown to be very sensitive, able to detect as little as 4.8 DNA copies number μL −1 . In addition, the assay was found to have a high degree of repeatability and reproducibility, with a linear dynamic range ( R 2 = 0.999) extending over 6 log 10 dilutions and a high efficiency (100%). The assay was applied to DNA samples extracted from 48 formalin‐fixed paraffin‐embedded (FFPE) Atlantic salmon, Salmo salar, gill tissues showing varying degrees of gill pathology (scored 0–3) and from 26 jellyfish samples belonging to the species Phialella quadrata and Muggiaea atlantica . For each sample, the bacterial load was normalised against the level of the salmonid elongation factor alpha 1 (ELF) detected by a second real‐time PCR using previously published primers and probe. Tenacibaculum maritimum DNA was detected in 89% of the blocks with no signs of gill disease as well as in 95% of the blocks with mild‐to‐severe gill pathology. Association between bacterial load and gill pathology severity was investigated. T. maritimum DNA was detected at low level in four of the 26 jellyfish tested.

Use of Integrated Landscape Indicators to Evaluate the Health of Linked Watersheds and Coral Reef Environments in the Hawaiian Islands - Ku‘ulei S. Rodgers; Michael H. Kido; Paul L. Jokiel; Tim Edmonds; Eric K. Brown (Environmental Management, 2012)

Design and Performance of Pilot-Scale Constructed Wetland Treatment Systems for Treating Oilfield Produced Water from Sub-Saharan Africa - Jennifer E. Horner; James W. Castle; John H. Rodgers; Cynthia Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2012)

Responses of Lyngbya wollei to Exposures of Copper-Based Algaecides: The Critical Burden Concept - W. M. Bishop; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 2012)

Treatment of Selenium in Simulated Refinery Effluent Using a Pilot-Scale Constructed Wetland Treatment System - Michael M. Spacil; John H. Rodgers; James W. Castle; Cynthia L. Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2011)

A comparative analysis of sperm storage and mating strategies in five species of brachyuran crabs - Paula J. Rodgers; Marjorie L. Reaka; Anson H. Hines (Marine Biology, 2011)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

The path to preservation: Using proteomics to decipher the fate of diatom proteins during microbial degradation - Brook L. Nunn; Ying S. Ting; Lars Malmström; Yihsuan S. Tsai; Angela Squier; David R. Goodlett; H. Rodger Harvey (Limnology and Oceanography, 2010)
We drew upon recent advances in tandem mass spectrometry‐based proteomic analyses in order to examine the proteins that remain after a diatom bloom enters the stationary phase, precipitates out of the photic zone, and is subjected to microbial degradation over a 23‐d period within a controlled laboratory environment. Proteins were identified from tandem mass spectra searched against three different protein databases in order to track proteins from Thalassiosira pseudonana and any potential bacterial contributions. A rapid loss of diatom protein was observed over the incubation period; 75% of the proteins initially identified were not detected after 72 h of exposure to a microbial population. By the 23rd day, peptides identified with high confidence correlated with only four T. pseudonana proteins. Five factors may have influenced the preservation of diatom proteins: (1) protection within organelles or structures with multiple membranes, (2) the relative cellular abundance in the photosynthetic apparatus, (3) the number of transmembrane domains in the protein sequence, (4) the presence of glycan modification motifs, and (5) the capability of proteins or peptides to aggregate into supramolecules.

Characterization of Ash-Basin Waters from a Risk-Based Perspective - Lane Dorman; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Role of Equalization Basins of Constructed Wetland Systems for Treatment of Particulate-Associated Elements in Flue Gas Desulfurization Waters - Meg M. Iannacone; James W. Castle; John H. Rodgers (Water, Air, & Soil Pollution, 2009)

Source mechanisms of the June 2004 Tabuk earthquake sequence, Eastern Red Sea margin, Kingdom of Saudi Arabia - K. S. Aldamegh; K. M. Abou Elenean; H. M. Hussein; A. J. Rodgers (Journal of Seismology, 2009)

Comparative lipid dynamics of euphausiids from the Antarctic and Northeast Pacific Oceans - Se-Jong Ju; Hyung-Ku Kang; Woong Seo Kim; H. Rodger Harvey (Marine Biology, 2009)

The Impact of Hurricane Katrina on the Coastal Vegetation of the Weeks Bay Reserve, Alabama from NDVI Data - John C. Rodgers; Adam W. Murrah; William H. Cooke (Estuaries and Coasts, 2009)

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

Chemical, Physical, and Risk Characterization of Natural Gas Storage Produced Waters - Brenda M. Johnson; Laura E. Kanagy; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Erythrocytic inclusion body syndrome virus in wild Atlantic salmon, Salmo salar L. - H D Rodger (Journal of Fish Diseases, 2007)
An investigation was undertaken to establish aspects of the epizootiology of erythrocytic inclusion bodies in wild Atlantic salmon, Salmo salar L., in Scotland. From 1992 to 1995, adult and juvenile salmon, from Scottish rivers, were screened for the presence of erythrocytic inclusion bodies and haematological parameters measured. The nature of the inclusion bodies was assessed through transmission electron microscopy, negative‐staining and blood smear‐staining techniques and was demonstrated to be viral in origin with characteristics similar to a member of the family Togaviridae. Specifically, these were a viral genome of single‐stranded RNA, spherical virion morphology with an icosahedral core, average size of 70 nm and a buoyant density of 1.15–1.20 g cm −3 . The cytoplasmic inclusions were either large, single inclusions (1–2 μm) or smaller multiple inclusions (0.5–1 μm). A total of 4.2% ( n = 48) and 27.7% ( n = 213) of the parr and adult salmon, respectively, were positive for the presence of the inclusions. The intensity of the inclusions, when present, varied from light in parr to moderate and heavy in adults, when graded according to the number of inclusions per field of view. Neither haematological variations nor clinical disease was associated with the presence or absence of viral inclusions.

Epidemiological observations of pancreas disease of farmed Atlantic salmon, Salmo salar L., in Ireland - H Rodger; S Mitchell (Journal of Fish Diseases, 2007)
Epidemiological investigations into the pancreas disease (PD) of farmed salmon were conducted on populations of Atlantic salmon reared in Ireland during 2003 and 2004. The investigations surveyed all marine salmon farms operating in Ireland through a detailed questionnaire with follow‐up farm visits. Information was gathered on 21 populations of fish in 2003 and 14 populations in 2004. Thirteen of the 21 populations suffered PD in 2003 and 12 of the 14 in 2004. The mean mortality due to PD on affected farms was 18.8% in 2003 and 14.8% in 2004 and the loss of growth due to PD was estimated at 11.4% over the 2‐year period. The highest risk periods for outbreaks of PD were early summer and early autumn and the farms most seriously affected by PD mortality were in the western counties of Ireland. Factors which showed an indication of association with a PD outbreak or high mortality during a PD outbreak were: livestock movement to another sea site, high feeding rate prior to any PD outbreak, the presence of another PD positive farm in the same water body, greater than 250 000 fish on a site, a previous history of PD on a site, a high sea lice burden, and sites located in the western regions of Ireland which reared a specific strain of salmon.

Longitudinal serological surveys of Atlantic salmon, Salmo salar L., using a rapid immunoperoxidase‐based neutralization assay for salmonid alphavirus - D A Graham; V A Jewhurst; H M Rowley; M F McLoughlin; H Rodger; D Todd (Journal of Fish Diseases, 2005)
Longitudinal serological surveys for salmon pancreas disease virus (SPDV), the causal agent of pancreas disease (PD), were conducted on multiple caged populations of Atlantic salmon, Salmo salar L., on two farms over a 77‐week period (farm 1, freshwater and marine stages) and a 36‐week period (farm 2, marine stage only), using a microtitre‐based virus neutralization (VN) assay. Collected sera were also screened for viraemia with SPDV, and pancreas, heart and muscle tissues were examined for lesions consistent with PD. Outbreaks of PD occurred during the marine phase on both farms, as demonstrated by seroconversion, the isolation of virus and progressive histopathological changes consistent with a PD outbreak. All populations monitored showed a progressive increase in seroprevalence of 90–100%, typically accompanied by rises in geometric mean antibody titres. With the exception of one caged population, which showed a marked biphasic seroprevalence pattern, the seroprevalence figures in the remaining four monitored populations remained high (≥70%) until the end of the study period. Peak VN titres of ≥1/1280 were detected on both farms. The results provide essential baseline information for the interpretation of SPDV VN serology results, and indicate that this methodology is suited to both the diagnosis and seroepidemiology of SPDV infections.

Contributions of Schoenoplectus californicus in a Constructed Wetland System Receiving Copper Contaminated Wastewater - Cynthia L. Murray-Gulde; George M. Huddleston; Kristina V. Garber; John H. Rodgers (Water, Air, & Soil Pollution, 2005)

Understanding the trophic role of the Antarctic ctenophore, Callianira antarctica, using lipid biomarkers - Se-Jong Ju; K. Scolardi; K. L. Daly; H. Rodger Harvey (Polar Biology, 2004)

The Responses of Selected Terrestrial Plants to Short (<12 days) and Long Term (2, 4 and 6 Weeks) Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) Exposure. Part I: Growth and Developmental Effects - Linda E. Winfield; John H. Rodger; Stephen J. D'surney (Ecotoxicology, 2004)

Black carbon in estuarine and coastal ocean dissolved organic matter - Antonio Mannino; H. Rodger Harvey (Limnology and Oceanography, 2004)
We measured black carbon (BC) in ultrafiltered, high‐molecular weight dissolved organic matter (UDOM) in surface waters of Delaware Bay, Chesapeake Bay, and the adjacent Atlantic Ocean (U.S.A.) to investigate the importance of riverine and estuarine dissolved organic matter (DOM) as a source of BC to the ocean. BC was 5‐72% of UDOM‐C (27 ± 17%), which corresponds to 8.9 ± 6.5% of dissolved organic carbon (DOC), with higher values in the heavily urbanized midbay region of the Delaware Estuary and lower yields in the river and coastal ocean. The spatial and seasonal distributions of BC along the salinity gradient of Delaware Bay suggest that the elevated levels of BC in surface water UDOM originate from localized sources, possibly from atmospheric deposition or release from resuspended sediments. BC in UDOM made up 4–7% of the DOC in the coastal Atlantic Ocean, revealing that river‐estuary systems are important exporters of colloidal BC to the ocean. The annual flux of BC from Delaware Bay UDOM to the Atlantic Ocean was estimated at 2.4 x 10 10 g BC yr −1 , supporting the hypothesis that the DOC pool is an important contributor of BC to the ocean.

Fine root dynamics in two atlantic white-cedar wetlands with contrasting hydroperiods - H. LeRoy Rodgers; Frank P. Day; Robert B. Atkinson (Wetlands, 2003)

Algicidal Effectiveness of Clearigate, Cutrine-Plus, and Copper Sulfate and Margins of Safety Associated with Their Use - C. L. Murray-Gulde; J. E. Heatley; A. L. Schwartzman; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 2002)

Toxicity and Bioavailability of Copper Herbicides (Clearigate, Cutrine-Plus, and Copper Sulfate) to Freshwater Animals - B. J. Mastin; J. H. Rodgers, (Archives of Environmental Contamination and Toxicology, 2000)

Biochemical composition of particles and dissolved organic matter along an estuarine gradient: Sources and implications for DOM reactivity - Antonio Mannino; H. Rodger Harvey (Limnology and Oceanography, 2000)
The chemical composition of high molecular weight dissolved organic matter (DOM) and particulate organic matter (POM) was examined along the salinity gradient of the Delaware Estuary. DOM was collected and frac‐tionated by tangential‐flow ultrafiltration into 1–30 kDa (HDOM; high molecular weight) and 30 kDa to 0.2 mm (VHDOM; very high molecular weight) and compared to particles collected in parallel. Polysaccharides comprised 12–43% of particulate organic carbon (POC), 30–56% of VHDOM carbon, and 7.5–19% of HDOM carbon. Hydrolyzable amino acids comprised 17–38% of POC, 5.4–12% of VHDOM carbon, and 1.5–4.2% of HDOM carbon. Only 7–43% of dissolved organic nitrogen in VHDOM and HDOM consisted of amino acids, indicating that organic nitrogen is highly modified within the dissolved pool or an unidentified pool of dissolved organic nitrogen exists. The composition of amino acids and distribution of polysaccharides are consistent with enrichment of structural biopolymers from algae and vascular plants within DOM. Proteinaceous matter released during the growth of an axenic diatom culture contains similar amino acid distributions across size fractions as in Delaware Bay samples. The source of organic matter appears to be as important as microbial processing in determining amino acid content and composition of DOM. Shifts in amino acid composition point to contrasting sources and extent of degradation for organic matter along the estuarine gradient and among size fractions. The lower amino acid and carbohydrate content and higher b‐alanine content in HDOM suggests that this fraction is more highly degraded relative to POM and VHDOM and provides geochemical evidence in support of the size‐reactivity continuum hypothesis. Spatial patterns in reactivity of organic constituents were also evident with more degraded organic matter in the turbid middle estuary and the release of fresh DOM from diatoms in the lower estuary.

Effects of a Homologous Series of Linear Alcohol Ethoxylate Surfactants on Fathead Minnow Early Life Stages - R. E. Lizotte Jr.; D. C. L. Wong; P. B. Dorn; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Diseases of Puntazzo puntazzo Cuvier in marine aquaculture systems in Greece - F. Athanassopoulou; Th Prapas; H. Rodger (Journal of Fish Diseases, 1999)

Copper Bioavailability in Steilacoom Lake Sediments - D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Comparative Toxicity of Chlordane, Chlorpyrifos, and Aldicarb to Four Aquatic Testing Organisms - M. T. Moore; D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr.; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 1998)

Experimental Factors That May Affect Toxicity of Cadmium to Freshwater Organisms - B. C. Suedel; J. H. Rodgers Jr.; E. Deaver (Archives of Environmental Contamination and Toxicology, 1997)

Comparative Aqueous Toxicity of Silver Compounds: Laboratory Studies with Freshwater Species - J. H. Rodgers, Jr.; E. Deaver; B. C. Suedel; P. L. Rogers (Bulletin of Environmental Contamination and Toxicology, 1997)

Formulated sediment as a reference and dilution sediment in definitive toxicity tests - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Experimental factors that may affect toxicity of aqueous and sediment-bound copper to freshwater organisms - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Formulated Sediment as a Reference and Dilution Sediment in Definitive Toxicity Tests - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Experimental Factors That May Affect Toxicity of Aqueous and Sediment-Bound Copper to Freshwater Organisms - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Fate of endothall during the Pat Mayse Lake (Texas) aquatic plant management program - K. H. Reinert; M. L. Hinman; H. Rodgers (Archives of Environmental Contamination and Toxicology, 1988)

Effects of suspended solids on the bioavailability of chlordane toDaphnia magna - W. Scott Hall; Kenneth L. Dickson; Farida Y. Saleh; John H. Rodgers (Archives of Environmental Contamination and Toxicology, 1986)